Alternative biofuel materials for microbial fuel cells from poplar wood - Erensoy, Ahmet; Çek, Nurettin (My University, 2018)
In this study, biofuel properties of poplar wood materials rich in organic materials were investigated for microbial fuel cells. Therefore, in this study, investigates the chemical, biochemical properties with electrochemical performance of single chamber microbial fuel cell manufactured using poplar biomass materials, natural soil, graphite anode electrode and graphite cathode electrode. With the increase in the weight of the poplar tree in the microbial fuel cells, the power density increased. SEM, EDS, FTIR analyses showed that bacillus and coccus type bacteria in the natural structure of the soil act as the catalyst in the anode electrode. Poplar wood, electrodes and bacteria have served in harmony. According to experimental results, the maximum power reaches to 16.88?mW and microbial fuel cell successfully displays a maximum power density of 8555?mW/m2. All these results indicate that poplar wood may be appropriate biofuel sources for electrical energy generation as an effective environmentally microbial fuel cell technology.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Biomass; Environment friendly energy; Microbial fuel cell; Poplar